Sinus surgery complicated by ventricular fibrillation in a young patient: Inverted (reverse) Takotsubo cardiomyopathy - Demir, Gültekin Günhan; Güler Babür, Gamze; Güler, Ekrem; Güneş, Hacı Murat; Kızılırmak, Filiz (Turkish Soc Cardiology, 2016)
Takotsubo cardiomyopathy (TTC), also known as left ventricular apical ballooning syndrome or stress cardiomyopathy, is characterized by transient left ventricular systolic dysfunction and the absence of obstructive lesion in the epicardial coronary arteries. The most common presentation is acute substernal chest pain, although occasionally dyspnea and syncope, and rarely shock with ST-segment elevation and elevated cardiac biomarkers have been observed. Inverted (reverse) TTC is a rare pattern characterized hypokinesis of the basal and midventricular segments. Presently described was case of a 27-year-old woman with ventricular fibrillation following endoscopic nasal sinus surgery.

Takotsubo kardiyomiyopatisi (TTK), apikal balonlaşma veya stres kardiyomiyopatisi olarak da bilinmektedir ve epikardiyal koroner arterlerde kritik darlığın eşlik etmediği geçici sol ventrikül fonksiyonu bozukluğu ile kendini gösterir. En sık başvuru şekli akut substernal göğüs ağrısı, bazen ani nefes darlığı ve senkop ve nadiren de şok şeklinde olup tabloya ST-segment yükselmesi ve kardiyak biyobelirteçlerin yükselmesi eşlik eder. Ters TTK ise çok daha nadir görülür ve bazal ve/veya midventriküler segmentlerin hipokinezisi ile karakterizedir. Bu yazıda, kronik sinüzit ve nazal polip nedeniyle nazal sinüs cerrahisi geçiren ve cerrahi sonrası ventrikül fibrilasyonu gelişen 27 yaşındaki bir kadın hasta sunuldu
Genç bir hastada sinüs cerrahisi sonrası gelişen ventrikül fibrilasyonu: Ters takotsubo kardiyomyopatisi
WOS: 000380170200011
PubMed ID: 27439928
Keywords: Inverted Takotsubo Cardiomyopathy; Sinus Surgery; Ventricular Fibrillation; Ters Takotsubo Kardiyomiyopatisi; Sinüs Cerrahisi; Ventriküler Fibrilasyon